Editor’s Note - Devi, S. Susela; Chan, Wai Meng; Mohd Salleh, Noor Akma (Asian Journal of Business and Accounting, 2014)
It is our pleasure to present to you the first issue of Volume 7 of the Asian Journal of Business and Accounting (AJBA). The journal made its debut in 2008 and has continued to publish research work from scholars within Asia and elsewhere relating to issues in the Asian region. We are encouraged by submissions from scholars from many parts of the world and the growing interest in business and accounting research in this region. We are particularly pleased to receive papers from Asia, especially, the emerging economies. In this issue we have included papers from authors from Indonesia, Iraq, Malaysia, Saudi Arabia and South Korea. AJBA is already indexed in SCOPUS, ERA 2012, and MyCite with a 5 year impact factor of 0.093. We are hopeful given the rigour and quality of papers that have been published and also currently under review, that AJBA will soon succeed in its endeavour to be indexed in the Thomson Reuters Web of Science. In this issue six articles are presented. The first is by Ali Zwain et al. (2014) which investigates empirically the relationship between Total Quality Management (TQM) practices and organisational knowledge creation as perceived by academic leaders in Iraqi Higher Education Institutions (HEIs). The findings suggest that Iraqi HEIs benefit from practicing TQM. The study allows practitioners to gain in-depth knowledge regarding the impact of TQM practices in an educational setting. The next paper examines the market integration among 22 international markets from the perspective of Malaysian investors. Lee and Isa (2014) also analyse the impact of the subprime financial crisis of 2007-8 on the integration of these markets. They find that Malaysia was largely unrelated with other markets. The next paper, Choi and Yoon (2014) investigates whether audit quality, as proxied by Big N audit firms, and IFRS-related consulting services impact the relationship between IFRS adoption and audit fees. The authors find that Korean accounting firms affiliated with foreign Big N firms have a positive effect on the relationship between IFRS adoption and audit fees. The implications are that auditors can mitigate audit costs through the knowledge spillover effect between audit and consulting services regardless of independence impairment because they understand the internal control of auditees from their consulting experience. Next, Nurkholis et al. (2014) examine how regulation of performance measurement and goal orientation affects the utilisation of performance measurement in the Indonesian local government context. They find that the likelihood of actual implementation of performance measurement is stronger when there is strong goal orientation. This study contributes a model of regulatory-based performance in a developing country context. This is followed by Mohamed et al. (2014) who examine the relationship between strategic performance measurement systems (SPMS) and organisational capabilities: market orientation, organisational learning, innovation and entrepreneurship. They find that the beliefs and boundary control systems partly moderate the relationship between SPMS design and use, and innovation and entrepreneurship. The authors discuss the implications of these findings in the Malaysian context. The last paper is by Mohd-Saleh and Omar (2014). They use a sample of 948 firm years from 2006 to 2008 to examine whether the combined effect of CEO duality and family-controlled firms significantly impact the recognition of goodwill impairment. We take this opportunity to welcome the new Chief Editor, Che Ruhana Isa who takes over from Susela Devi, who has served AJBA since 2010 and has now retired from University of Malaya. Our sincere appreciation is extended to all our area editors, members of the editorial board and advisory board and reviewers for their continued support and encouragement. We hope this issue brings AJBA closer to achieving its mission to incrementally provide a voice for scholars embarking on Asia-focused research.